2015
DOI: 10.1785/0120150133
|View full text |Cite
|
Sign up to set email alerts
|

Seismometer Detection of Dust Devil Vortices by Ground Tilt

Abstract: We report seismic signals on a desert playa caused by convective vortices and dust devils. The long-period (10-100s) signatures, with tilts of ~10$^{-7}$ radians, are correlated with the presence of vortices, detected with nearby sensors as sharp temporary pressure drops (0.2-1 mbar) and solar obscuration by dust. We show that the shape and amplitude of the signals, manifesting primarily as horizontal accelerations, can be modeled approximately with a simple quasi-static point-load model of the negative pressu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 28 publications
1
61
0
1
Order By: Relevance
“…This simpler model gives very similar results, as described in Murdoch et al (2016a). The advantage of this simpler model is that it can be considered as validated on Earth: Lorenz et al (2015) has shown that the size and amplitude of seismic signal generated on a seismometer by a dust devil (which can be assimilated to a pressure point source) can be measured, and is consistent with the Greens' function approximation used. In purple (dashed), the estimated self-noise of the InSight flight model micro-barometer.…”
Section: Pressure Field Assumptionssupporting
confidence: 52%
“…This simpler model gives very similar results, as described in Murdoch et al (2016a). The advantage of this simpler model is that it can be considered as validated on Earth: Lorenz et al (2015) has shown that the size and amplitude of seismic signal generated on a seismometer by a dust devil (which can be assimilated to a pressure point source) can be measured, and is consistent with the Greens' function approximation used. In purple (dashed), the estimated self-noise of the InSight flight model micro-barometer.…”
Section: Pressure Field Assumptionssupporting
confidence: 52%
“…These systems have allowed large numbers (hundreds to thousands) of unperturbed vortex encounters to be obtained without chase biases, finally yielding robust statistics on vortex populations from pressure drops (Lorenz and Lanagan 2014; and on dust loading . Furthermore, the small measurement stations can be deployed in spatial arrays to make simultaneous measurements that resolve the two-dimensional horizontal structure of dust devils (Lorenz et al 2015a(Lorenz et al , 2015b(Lorenz et al , 2015c.…”
Section: Pressure Measurementsmentioning
confidence: 99%
“…Lorenz et al (2015b) employed another field site, La Jornada Experimental Range in New Mexico (operated by the US Department of Agriculture) where access is restricted and so larger installations can be left safely unattended.…”
Section: Pressure Measurementsmentioning
confidence: 99%
See 2 more Smart Citations